What Factors Influenced Students’ Decision to Choose Nursing? - Salminen-Tuomaala, Mari; Herttuala, Niina (European Journal of Applied Sciences, 2022)
Nursing staff shortage has become a serious challenge worldwide while the number of applicants for nursing courses is decreasing. The identification of factors for choosing the profession is important for planning recruitment strategies. This observational quantitative study presents nursing students’ perceptions of factors that had influenced their decision to apply for the nursing program. The aim is to produce knowledge that can be used to make the profession more attractive to potential workforce. Data was collected in March 2022 from 94 first, second and third-year nursing. The students responded to an online questionnaire with 12 quantitative items using the Likert rating. The data was analyzed using SPSS for Windows 27. Percentages, frequencies and measures of central tendency were used to present the results. The STROBE checklist for cross-sectional studies was used to help conduct the study. Intrinsic factors; desire to help the ill and suffering, in interaction with people, and the idea of being suited for the profession had been the most compelling motivators for the students. Some extrinsic factors; job security or favorable employment situation, had also significantly affected the students’ decision to apply to the nursing program. Professional prestige, the social media or other people’s opinions had not much affected the students’ decision to apply.